Problems and Obstacles in digital skills of court personnel Case Study : Yasothon Provincial Court - Sanitnit, Ratchadaphon; Sirpokangkul, Siwach (Journal of Modern Learning Development, 2023)
The objectives of this research were to study 1) Yasothon Provincial Court personnel’s current digital skills 2) Problems and obstacles in digital technology usage of Yasothon Provincial Court personnel 3) Guidelines for solving problems and obstacles in digital technology usage of Yasothon Provincial Court personnel. The researcher used a qualitative research methodology, collect information on academic documents, articles, official documents and collect data from in-depth interviews by using a specific method, which is selecting 10 people to summarize and analyze the problems, obstacles, and solutions for the court personnel’s digital skills. The results of the research were 1) Yasothon Provincial Court personnel’s current digital skills. Some personnel only have basic knowledge of digital technology usage, as well as personnel who are totally lack of digital skills. The court office has digital technology usage training every 6 months, more than 9 hours, to develop digital technology capabilities for personnel. And the digital technology systems that support operation is convenient to use, but some systems have problems. 2) Problems and obstacles in digital technology usage of Yasothon Provincial Court personnel. They are the personnel’s attitude towards digital technology, some personnel still lack of knowledge and understanding of digital technology usage, providing digital skills training that do not match the group, training period, and insufficient computer scholars in the system, lack of stability equipment and supplies only lasts for 7 years. 3) Guidelines for solving problems and obstacles in digital technology usage of Yasothon Provincial Court personnel are changing personnel’s attitudes toward digital technology, providing digital technology usage training in order to increase digital skills in workshop, arranging for individual performance examination, and increasing the number of computer scholars in the systems, merging the system into a single system, reducing the usage period of equipment and supplies to 3 – 4 years.